Safety profile of 185 ultrasound-guided intra-articular injections for treatment of rheumatic diseases of the hip - A. Migliore; S. Tormenta; L.S. Martin Martin; C. Valente; U. Massafra; A. Latini; A. Alimonti (PAGEPress Publications, 2004)
Objective: We have developed a standardized technique for intra-articular injection of the hip joint with the purpose of extending routine intra-articular injection of hyaluronans and steroids to the hip, as commonly used in the knee. The purpose of this study was to examine the safety of this technique in an extended series of patients. Methods: A 7 MHz linear or 3.5 MHz convex transducer was used with a sterilized biopsy guide attached. Intra-articular (IA) injection was performed by inserting into the biopsy guide a 20 gauge needle with the anterosuperior approach. Then, using biopsy real-time guidance software, the needle was advanced into the anterior capsular recess, at the level of the femoral head. Results: The standardised technique was used to inject 97 patients (114 hips) with 185 injections of either steroid/local anaesthetic (10) or hyaluronan (175) over a three-year period. The treatment was well tolerated with few, and exclusively local, side effects. No systemic side effects or joint infections were observed in our study. The colour Doppler vision allowed us to avoid injecting blood vessels. In all cases direct visualization of needle introduction and progression into the articular space was shown by on-screen guidance. Ultrasound guidance is more economic and faster in comparison to the TC or fluoroscopic guidance. Contrary to TC or fluoroscopic techniques ultrasound does not require use of radiations or iodized contrast. Conclusion: Our data suggest that the administration of hyaluronans or steroids with ultrasound-guided intra-articular injection is a safe technique for treatment of rheumatic diseases of the hip.